2023
DOI: 10.1039/d2cy02000a
|View full text |Cite
|
Sign up to set email alerts
|

Inserted hydrogen promotes oxidation catalysis of mixed Ru0.3Ti0.7O2 as exemplified with total propane oxidation and the HCl oxidation reaction

Abstract: The solid solution of a reducible oxide with a (non or) less reducible oxide may open the way to incorporate substantial amounts of hydrogen by the simple exposure to H2...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…In addition, the authors surmised that hydrogen was combined into the rutile lattice and changed the lattice parameters, leading to the reduce of the adsorption energy of chlorine. 22 This work indicated evidence for the significance of adjustment of the lattice parameters of RuO 2 in HCl catalytic oxidation.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…In addition, the authors surmised that hydrogen was combined into the rutile lattice and changed the lattice parameters, leading to the reduce of the adsorption energy of chlorine. 22 This work indicated evidence for the significance of adjustment of the lattice parameters of RuO 2 in HCl catalytic oxidation.…”
Section: Introductionmentioning
confidence: 69%
“…This effect has been identified in literature that RuO 2 lattice parameters are closely related to the difficulty of Cl 2 desorption, which is the rate-limiting step in HCl oxidation. In addition, Over et al also reported that the significantly increased activity of HCl oxidation was obtained on the H-doped Ru 0.3 Ti 0.7 O 2 with the changes of lattice parameters …”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…10 Besides, some economic and robust alternatives, such as CeO 2 , CeO 2 -MnO x , U 3 O 8 , Ru 0.3 Ti 0.7 O 2 , and CuCrO 2 , turned out to be promising Deacon catalysts, since they were active and stable at elevated reaction temperatures. [11][12][13][14][15][16][17][18] In the last decade, a major breakthrough in the Deacon process has been achieved with the development of TiO 2 (rutile) or SnO 2 (cassiterite) supported RuO 2 catalysts, which have shown a high activity at a low temperature and a remarkable stability against chlorination and sintering of the active RuO 2 species on the supports. [19][20][21][22][23] However, these benchmark catalysts are easily deactivated in the catalytic oxidation of HCl with a small amount of HF, because their supports react with HF under the oxidation reaction conditions.…”
Section: Introductionmentioning
confidence: 99%